2020
DOI: 10.1108/lm-08-2019-0057
|View full text |Cite
|
Sign up to set email alerts
|

Toward becoming an inclusive library

Abstract: PurposeThe library's role in promoting and supporting the United Nations Agenda for Sustainable Development Goal (SDG) is beyond borders. It has the capacity to be a powerful driving force in leading exemplary programs that will transform society in many dimensions. This paper will share the value of libraries in integrating SDG's into their work and how it can positively advocate for change toward attaining an inclusive, open and tolerant society.Design/methodology/approachThis survey research and program eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“… 6 Endocrine therapy is associated with a significant increase in both progression-free survival (PFS) and overall survival (OS). 7 However, ET resistance and disease progression are the main causes of recurrence and death of patients. 1 , 6 Ongoing alternative strategies are being explored to improve outcomes among these patients.…”
Section: Introductionmentioning
confidence: 99%
“… 6 Endocrine therapy is associated with a significant increase in both progression-free survival (PFS) and overall survival (OS). 7 However, ET resistance and disease progression are the main causes of recurrence and death of patients. 1 , 6 Ongoing alternative strategies are being explored to improve outcomes among these patients.…”
Section: Introductionmentioning
confidence: 99%
“…All publications were focused directly on the HL events, except that two studies respectively reported on the development of a data system for managing HL resources [31] and a content analysis of documents about HL standards [18]. Fourteen (61%) publications were descriptive in nature [12][13][14]16,17,19,22,[25][26][27][30][31][32]34], most of which aimed to "describe", "overview", "review", "reflect on", or "discover" the HL approach and reported on the implementation, process, and experience of HL events. Many of their research methodologies are of questionable quality, as they did not describe the exact research designs, mentioned the use of case study without details, or used generic methods to collect the outcomes or observations after an HL (e.g., only post-event survey, observation, or interview).…”
Section: Publication Characteristics Study Objectives and Research De...mentioning
confidence: 99%
“…The reported HLs were held in enclosed spaces. The majority of HLs were reportedly held in physical libraries, such as those associated with universities [14,16,17,19,22,24,25,34] and public libraries [14,17,20,32]. Other venues were primarily in educational settings, including university venues or facilities, student or information centers, and classrooms [17,21,24,28,34].…”
Section: Venue and Modementioning
confidence: 99%
See 1 more Smart Citation
“…Libraries play a role in integrating SDG's to be able to advocate for positive change to achieve an inclusive, open, and tolerant society [14,15]. Publiclibrary teachers in the U.S. are engaged in environmental education and are looking for new strategies for teaching information literacy [16,17].…”
Section: Introductionmentioning
confidence: 99%